2018
DOI: 10.1186/s13104-018-3139-6
|View full text |Cite|
|
Sign up to set email alerts
|

Antihypertensive medication adherence and associated factors among adult hypertensive patients at Jimma University Specialized Hospital, southwest Ethiopia

Abstract: BackgroundAdherence to antihypertensive medications is a key component to control blood pressure levels. Poor adherence to these medications leads to the development of hypertensive complications and increase risk of cardiovascular events which in turn reduces the ultimate clinical outcome. The purpose of this study was to assess antihypertensive medication adherence and associated factors among adult hypertensive patients. A hospital-based cross-sectional study among adult hypertensive patients was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
83
4
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(102 citation statements)
references
References 35 publications
12
83
4
3
Order By: Relevance
“…A study carried out in Taiwan (22) identified significantly worse adherence to treatment among non-frail patients, while researchers in Poland (17) found the highest frailty scores among older adult patients, being considered a determining factor of less adherence to treatment. As in this study, there are publications which do not report a correlation between frailty and adherence (12,27) .…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…A study carried out in Taiwan (22) identified significantly worse adherence to treatment among non-frail patients, while researchers in Poland (17) found the highest frailty scores among older adult patients, being considered a determining factor of less adherence to treatment. As in this study, there are publications which do not report a correlation between frailty and adherence (12,27) .…”
Section: Introductionmentioning
confidence: 61%
“…In a study in Taiwan (22) , the best adherence to treatment was related to frail patients with advanced age, as they are more attentive to their health and more compliant with the prescribed treatments. According to researchers from Ethiopia (27) , developed and developing countries have better healthcare and differentiated access to health facilities, constituting elements which positively affect adherence in comparison with this study and those carried out in countries with difficult access to health services.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…After publication of our article [ 1 ] we became aware that we had not obtained permission to reproduce the questions from the eight-item Morisky’s Medication Adherence Scale. The table in this Correction replaces Table 2 in our article.…”
Section: Correction To: Bmc Res Notes (2018) 11:27 101186/s13104-018mentioning
confidence: 99%
“…Data from hypertension clinics in large referral hospitals based in urban centres suggest that factors such as age, knowledge about the disease, distance from the hospital and the presence of comorbidities are all predictors of patient adherence. 10,[13][14][15] Little is known, however, about the retention of hypertensive patients in rural populations, where the reasons are likely to be different. While financial difficulties, knowledge of the disease, poor social support, stigma and the occurrence of side effects have been identified as factors affecting adherence in epilepsy patients attending urban clinics, 16,17 data concerning rural epilepsy patients are sparse, although there are suggestions that the determinants of LTFU in rural areas may be different.…”
mentioning
confidence: 99%